A Reflection on Interactional Feedback by Students of Sanata Dharma University - Sandy Ferianda; Herdiyanti Herdiyanti (Faculty of Social and Political Sciences University of Bangka Belitung, 2019)
Interactional feedback as a means of helping second language (L2) learners to focus on form has received increased attention recently in the field of second language acquisition (SLA). Moreover, feedback is also considered as an effective way to help the students improve their ability in learning L2. Subsequently, as teachers encourage use of the target language in their classrooms, they must consider how to provide feedback to their students concerning the accuracy of their utterances. This paper attempts to reveal the answers for the research question which is “what does interactional feedback mean to the students?” There are two participants who were willing to share their lived experiences. The data are in a form of texts and gathered from an in-depth interview in which the data are then extracted to be the themes for the discussion. For the themes, there are two major themes appear in the study namely motivation and self-improvement. Motivation was the first theme that appeared from the study. The comments and feedback could motivate the participants to perform better in their next speaking practices. Additionally, motivation indeed becomes one of the positive effects which could make the participants feel motivated in improving their speaking ability through the feedback from their lecturers. Self-improvement became the second major theme from the study. Self-improvement was derived from the participants’ consciousness when they encountered the mistakes that they often committed when speaking. Contextually, the interactional feedback that the participants gained from the lecturer made the participants aware of the mistake that they had committed. Therefore, after gaining the feedbacks from their teacher, they are triggered to improve their performance in the next speaking assignments.